Myeloid cells, BAFF, and IFN-γ establish an inflammatory loop that exacerbates autoimmunity in Lyn-deficient mice - Scapini, Patrizia (The Rockefeller University Press, 2010)
Autoimmunity is traditionally attributed to altered lymphoid cell selection and/or tolerance, whereas the contribution of innate immune cells is less well understood. Autoimmunity is also associated with increased levels of B cell–activating factor of the TNF family (BAFF; also known as B lymphocyte stimulator), a cytokine that promotes survival of self-reactive B cell clones. We describe an important role for myeloid cells in autoimmune disease progression. Using Lyn-deficient mice, we show that overproduction of BAFF by hyperactive myeloid cells contributes to inflammation and autoimmunity in part by acting directly on T cells to induce the release of IFN-γ. Genetic deletion of IFN-γ or reduction of BAFF activity, achieved by either reducing myeloid cell hyperproduction or by treating with an anti-BAFF monoclonal antibody, reduced disease development in lyn(−/−) mice. The increased production of IFN-γ in lyn(−/−) mice feeds back on the myeloid cells to further stimulate BAFF release. Expression of BAFF receptor on T cells was required for their full activation and IFN-γ release. Overall, our data suggest that the reciprocal production of BAFF and IFN-γ establishes an inflammatory loop between myeloid cells and T cells that exacerbates autoimmunity in this model. Our findings uncover an important pathological role of BAFF in autoimmune disorders.